2000
DOI: 10.1073/pnas.100132197
|View full text |Cite
|
Sign up to set email alerts
|

Galactolipid deficiency and abnormal chloroplast development in the Arabidopsis MGD synthase 1 mutant

Abstract: The lipid monogalactosyl diacylglycerol (MGD) is a major structural component of photosynthetic membranes in chloroplasts. Its formation is catalyzed by the enzyme MGD synthase. In many plants, MGD derives from two different biosynthetic pathways: the prokaryotic pathway, which operates entirely within the plastid, and the eukaryotic pathway, which involves steps in the endoplasmic reticulum. Here, we describe the identification and characterization of an Arabidopsis mutant with a defective MGD synthase gene (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
222
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 265 publications
(234 citation statements)
references
References 38 publications
12
222
0
Order By: Relevance
“…These results are consistent with previous studies that indicated a role for MGDGs and DGDGs in the structure of thylakoid membranes (Dörmann et al, 1995;Jarvis et al, 2000). In this study, we observed a significant reduction of grana stacks per chloroplast in NE compared with IE poplar lines (Fig.…”
Section: Suppression Of Isoprene Biosynthesis Decreases the Chloroplasupporting
confidence: 83%
“…These results are consistent with previous studies that indicated a role for MGDGs and DGDGs in the structure of thylakoid membranes (Dörmann et al, 1995;Jarvis et al, 2000). In this study, we observed a significant reduction of grana stacks per chloroplast in NE compared with IE poplar lines (Fig.…”
Section: Suppression Of Isoprene Biosynthesis Decreases the Chloroplasupporting
confidence: 83%
“…1 I) is impaired and 16-carbon fatty acid-containing lipids are decreased (13). The mgd1 mutant of Arabidopsis deficient in MGDG synthase activity revealed that MGD1 is responsible for the bulk of MGDG biosynthesis (14), whereas the dgd1 mutant phenotype suggested that the DGD1 gene product (Fig. 1) is responsible for over 90% of DGDG biosynthesis (15).…”
mentioning
confidence: 99%
“…Thylakoid membrane lipids are central to photosynthetic function, including the stabilization of photosynthetic complexes and oxygen evolution (Jarvis et al, 2000;Jones, 2007;Leng et al, 2008;Mizusawa and Wada, 2012;Boudière et al, 2013). The most abundant classes are the neutral lipids monogalactosyldiacylglycerol (MGDG) and digalactosyldiacylglycerol (DGDG) and the anionic lipids sulfoquinovosyldiacylglycerol (SQGD) and phosphatidylglycerol (PG; Frentzen, 2004;Shimojima et al, 2010;Mizusawa and Wada, 2012).…”
mentioning
confidence: 99%